Chinese Voices in a Canadian Secondary School Landscape - Minichiello, Diane (Canadian Journal of Education/Revue canadienne de l'éducation, 2001)
In this article, I describe the adjustment experiences of 23 Chinese-speaking, foreign-born high-school students in Vancouver, where they are members of the largest school cultural group. During interviews, participants suggested their large numbers enabled them to reproduce their home community in Canada. Students chose behaviours that hindered their adjustment and adaptation. They did not form Canadian friendships, learn English easily, make cross-cultural adaptations, or excel in school. Students’ responses raise questions about the direction of Canadian education, the evolution of Canada’s pluralistic society, and the obligation of the education system to familiarize students with Canadian democratic life. L’étude porte sur les problèmes d’adaptation de 23 élèves sinophones, nés à l’étranger et fréquentant une école secondaire de Vancouver. Invoquant le fait qu’ils constituent le groupe culturel le plus important, ils se disent en droit de reproduire au Canada leur communauté d’origine et refusent de s’intégrer, soit socialement, soit en apprenant l’anglais. Leurs réponses suscitent des questions au sujet de l’orientation de l’enseignement, de l’évolution du pluralisme et de l’obligation du système d’éducation de familiariser les élèves avec la vie démocratique canadienne